Life Design-Ethics-Religion Studies: non-confessional RE in Brandenburg (Germany) - Kenngott, Eva-Maria (British journal of religious education, 2017)
"Life Design-Ethics-Religion Studies" (LER) is the only non-confessional form of religious education (RE) in Germany. Six years after German reunification, the federal state of Brandenburg introduced LER with its dimension of non-confessional RE into the school curriculum. In this contribution, LER will be elucidated in three steps. First, the focus will be on LER as an integrative concept encompassing (a) an integration of mainly philosophical investigation as well as religious issues and (b) social integration, in a course where secular pupils and those of different denominations learn together. Second, I will describe how this new concept brought about a break with the long history of confessional RE in Germany and realised the precept of neutrality of religious education provided by the State. Finally, I will examine how the subject was accompanied by a new understanding of RE and how the concept of "Religion Studies" is related to the concepts of "Ethics" and "Life Design". Here, attention will also be given to the competences that can be specified for LER.